ALASAN TIONGKOK MENGHENTIKAN IMPOR SAMPAH PLASTIK POLIETILENA TEREFTALAT (PET) TAHUN 2018 - Bharata W, A.A Gede Agung; Dharmiasih, D.A Wiwik; Widya Nugraha, A.A Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This paper seeks to explain the reason behind China’s decision to ban plastic waste import in 2018. China’s import on plastic waste were increasing significantly since 200 Within ten year since 2006, China imported half of world’s plastic waste. China’s recycling industry turned plastic waste into synthetic fiber called polyester. However, since 2018 China decided to ban plastic waste import. This research is analyzed using qualitative research methodology with secondary data collection focusing on state level analysis. This paper refers to two conceptual frameworks, which are rational choice actor and environmental security. The findings on this research leads to a conclusion that explains China’s decision is based on its profit calculation from textile industry and plastic waste recycling. Key words: Plastic waste, rational actor choice, environmental problem, and health issue.